2021
DOI: 10.1039/d0nj05457g
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of luminescence properties for [cyclometalated]-PtII(isocyanide) complexes upon co-crystallisation with halosubstituted perfluorinated arenes

Abstract: C–X⋯Cl–Pt Halogen bonds and πh⋯dz2[PtII] contacts led to the 2-fold increase of phosphorescence quantum yields for [cyclometalated]-PtII(isocyanide) complexes upon co-crystallisation with halosubstituted perfluorinated arenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…The increasingly growing interest towards halogen bonding (abbreviated as HaB) is related to its role in crystal engineering, 1 materials science, [2][3][4] noncovalent catalysis, 5 and human physiology. 6 HaB affects the solubility, 7,8 melting points, 9 thermal expansion, [10][11][12][13] color, 14,15 and also luminescence, 4,[16][17][18][19][20][21][22][23][24][25][26][27][28] sensing, 29,30 biological, 31 or magnetic 32 properties of chemical compounds and assemblies thereof.…”
Section: Introductionmentioning
confidence: 99%
“…The increasingly growing interest towards halogen bonding (abbreviated as HaB) is related to its role in crystal engineering, 1 materials science, [2][3][4] noncovalent catalysis, 5 and human physiology. 6 HaB affects the solubility, 7,8 melting points, 9 thermal expansion, [10][11][12][13] color, 14,15 and also luminescence, 4,[16][17][18][19][20][21][22][23][24][25][26][27][28] sensing, 29,30 biological, 31 or magnetic 32 properties of chemical compounds and assemblies thereof.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies of crystal engineering towards the design of solids with controllable structure and tunable physicochemical properties are amongst the well-recognized tools for material chemistry [1][2][3][4][5]. The emergence of halogen bonding (HaB; for reviews on HaB see references [6][7][8][9][10]) during the construction of supramolecular aggregates opens up a route for the optimisation of their valuable properties, such as catalytic activity [11][12][13][14][15], solubility [16,17], melting point [18], thermal expansion [19][20][21][22], colour [23][24][25][26][27], luminescence [28][29][30][31][32][33][34][35][36][37][38][39][40][41], sensing [42,43], biological [44], and magnetic [45] properties. Various tectons [46], including organic species or metal complex...…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 7c , 7e , 7i , 16 On the other hand, isocyanides are versatile synthons for photoluminescent platinum complexes, which show stimuli response properties, 17 and on some occasions, the luminescence can be modulated by noncovalent interactions. 18 In this field, some chromic cycloplatinated complexes containing the strong field ligand isocyanides have been documented, 14a , 19 and it has been demonstrated that their photophysical properties can be modulated effectively by adjusting steric effects, the strength of the intermolecular interactions, or the medium. In this line, our group has reported two families of chloro-cyclometalated complexes, the benzoquinolinyl [Pt(bzq)Cl(CNR)], 14a in which isocyanide was varied, [R = tert -butylisocyanide (Bu t ); 2,6-dimethylphenyl (Xyl); 2-naphthyl (2-Np)], and the xylylisocyanide compounds, [Pt(C ∧ N)Cl(CNXyl)], in which the cyclometalated backbone was modified [HC ∧ N = 2-phenylpyridine (ppy); 2,4-difluorophenylpyridine (dfppy); and phenylquinoline (pq)], 19a aiming to examine the role of the intermolecular π···π and short- or long-range Pt···Pt stacking interactions on their structural arrays and photophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among chromic Pt II systems, a number of cyclometalated Pt II complexes have been developed as a means to achieve bright, colorful luminescent materials. ,,,,, On the other hand, isocyanides are versatile synthons for photoluminescent platinum complexes, which show stimuli response properties, and on some occasions, the luminescence can be modulated by noncovalent interactions . In this field, some chromic cycloplatinated complexes containing the strong field ligand isocyanides have been documented, , and it has been demonstrated that their photophysical properties can be modulated effectively by adjusting steric effects, the strength of the intermolecular interactions, or the medium.…”
Section: Introductionmentioning
confidence: 99%